Poluição sonora: uma análise da percepção dos frequentadores do centro de Itapipoca - Ce - Araújo, Ilana Silva (2014)
This study analyzed the noise pollution in Itapipoca downtown, Ceará. It was based on the perception of local regulars. We attempted to investigate some passers-by’s perceptions of environmental issues, types of noise and their possible consequences for human health, besides the citizens’ willingness to pay for an environmental education program to reduce noise pollution and also socioeconomic description of the them. An authorial 30 question survey for 30 people was applied to collect some data. The respondents were divided into groups of residents, traders and/or workers crossing the center of the city, in which more than a half stated that they attend the studied place every day. It was also pointed the age of respondents, monthly income and schooling. Most of them proved to be conscious of environmental and noise pollution harm. The questionnaires exposed that the interviewees consider the noise to be a local problem and they feel annoyed by it. The perception of local noise, advertisements by sellers and the car sounds were more focused. The irritability and headache were the two main reactions on population. According to some results, the people who were interviewed were able to pay for the environmental education program and the amount of money suggested was about seven reals. The evaluation of results certifies that the passers-by are sensible and conscious of the effects caused by noise, as well as the disturbances in people’s health and welfare.